Pemikiran A.Chaedar Al-Wasilah tentang Pendekatan Literasi (Genre-Based Approach) dan Pembelajaran Bahasa Arab - Mutmainah, Fatimah Azzahra (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2018)
Abstract: Chaedar Alwasilah is a scholar who often voiced the importance of writing. He proposed two terms as an implication of discourse studies, the literacy literacy approach and the genre-based approach. This is the main point in writing this article, whether these two terms have the same or different implications in language learning. By using descriptive analysis method, the author tries to connect the two terms with Arabic learning. The results show that literacy and genre based approach are different. However, these two terms have the same intentions, such as the emphasis on the importance of writing skills. In relation to Arabic, although the term literacy approach is less well known, this article shows that the concept has also existed in Arabic learning. Keywords: Chaedar Alwasilah, Literacy Approach, Genre-Based Approach